Discordance Between Glucose Levels Measured in Interstitial Fluid vs in Venous Plasma After Oral Glucose Administration: A Post-Hoc Analysis From the Randomised Controlled PRE-D Trial - Færch, Kristine; Amadid, Hanan; Bruhn, Lea; Clemmensen, Kim Katrine Bjerring; Hulman, Adam; Ried-Larsen, Mathias; Blond, Martin Bæk; Jørgensen, Marit Eika; Vistisen, Dorte (Frontiers in Endocrinology, 2021)
Aims: The oral glucose tolerance test (OGTT) is together with haemoglobin A1c (HbA1c) gold standard for diagnosing prediabetes and diabetes. The objective of this study was to assess the concordance between glucose values obtained from venous plasma versus interstitial fluid after oral glucose administration in 120 individuals with prediabetes and overweight/obesity. Methods: 120 adults with prediabetes defined by HbA1c 39-47 mmol/mol and overweight or obesity who participated in the randomised controlled PRE-D trial were included in the study. Venous plasma glucose concentrations were measured at 0, 30, 60 and 120 minutes during a 75 g oral glucose tolerance test (OGTT) performed on three different occasions within a 26 weeks period. During the OGTT, the participants wore a CGM device (IPro2, Medtronic), which assessed glucose concentrations every five minute. Results: A total of 306 OGTTs with simultaneous CGM measurements were obtained. Except in fasting, the CGM glucose values were below the OGTT values throughout the OGTT period with mean (SD) differences of 0.2 (0.7) mmol/L at time 0 min, -1.1 (1.3) at 30 min, -1.4 (1.8) at 60 min, and -0.5 (1.1) at 120 min). For measurements at 0 and 120 min, there was a proportional bias with an increasing mean difference between CGM and OGTT values with increasing mean of the two measurements. Conclusions: Due to poor agreement between the OGTT and CGM with wide 95% limits of agreement and proportional bias at 0 and 120 min, the potential for assessing glucose tolerance in prediabetes using CGM is questionable.